Renewable Energy-Based Hybrid Power Systems for off-grid Base Transceiver Stations - a case study of BTS site in Kajiado County - Kiarie, A. B (Strathmore University, 2025)
This study explores the technical and economic feasibility of deploying a renewable hybrid power system comprising solar photovoltaic (PV), battery storage, and hydrogen fuel cells for powering off-grid Base Transceiver Stations (BTS) in Kenya. Motivated by the environmental impact and high operational costs of diesel generators currently used as backup power sources in telecommunications infrastructure, the research proposes an alternative energy solution aligned with Kenya’s carbon reduction targets under the Nationally Determined Contributions (NDC). A case study of a BTS site in Kajiado County was used to evaluate the proposed hybrid configuration. The system was modelled and simulated using MATLAB/Simulink to assess power flow, fuel cell activation, battery state of charge, and solar irradiance behaviour. HOMER software was used for system optimization and economic analysis, incorporating real load data, solar resource inputs, and cost parameters. Results indicate that the hybrid system meets energy demands reliably, with solar PV supplying most of the energy, batteries stabilizing supply, and the proton exchange membrane fuel cell (PEMFC) acting as a backup. The proposed system achieves an annual electricity output of approximately 67.43 MWh, with a Levelized Cost of Electricity (LCOE) of $0.351/kWh and a Net Present Cost (NPC) of $87,404 lower than the $102,253 NPC of a diesel-based system. Additionally, the system significantly reduces carbon emissions and fuel dependency. The findings demonstrate that integrating hydrogen fuel cells with solar and battery systems can provide a sustainable, cost-effective power solution for off-grid telecom sites. The study supports broader adoption of clean energy in Kenya’s telecommunications sector and contributes to climate action and energy access goals.
Full - text thesis